Analysis of Corporate Value in Manufacturing Companies - Supriandi Supriandi; Yusuf Iskandar; Ujang Setiawan (Future Science, 2020)
This study aims to be able to find out and provide information on the development of manufacturing industries that dominate companies registered in the Indonesian Securities Foam (BEI) to find out the value of the company in the Consumer Goods Consumer Cosmetics and Household Utilities Industry sector. Method: The author in this study uses a measurement tool to determine the value of the company that is the Tobins'Q ratio, Data Analysis: This study used 7 comics and household goods sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2017-2019 with information that can be accessed on the official website www.idx.com. Results and Discussion: The results of this study indicate that there are still companies that have a company value below one or are categorized as a low company (undervalued), but of 7 companies 5 companies have a Tobins'Q value of above 1 which means it has the potential to have potential growth. Conclusion: The author is optimistic that the Cosmetics and Households Sub-sector companies have better growth potential in the future and can have Tobins'Q values ??above 1 for 7 of these companies, the authors have the view that the stock prices that have been published by manufacturing companies are sufficient good but every year it fluctuates, increasing company performance to get high company value must be increased so that the company's profitability increases every year.